Pengaruh DER dan ROE Terhadap PBV pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Putu Sindiani; Idham Masri Ishak; Djoko Lesmana Radji (Masyarakat Ekonomi Syariah Bogor, 2024)
This research aims to determine the influence of Capital Structure and Profitability on company value in manufacturing companies in various industrial sectors for the 2018-2022 period. The sampling technique taken in this research used purposive sampling, the number of samples taken in this research was 37 companies. The data collection technique in this research uses secondary data, namely in financial reports that have been published by companies in various industrial sectors on the Indonesia Stock Exchange (BEI). The analytical tests used in this research are using multiple limear regression analysis, classical assumption testing, and hypothesis testing. The research results show that: 1) Capital structure partially influences company value. 2) Profitability personally influences company value. 3) Simultaneously, capital structure and profitability influence company profitability.